Folate-targeting annonaceous acetogenins nanosuspensions: significantly enhanced antitumor efficacy in HeLa tumor-bearing mice - Haowen Li; Yijing Li; Hui Ao; Dongdong Bi; Meihua Han; Yifei Guo; Xiangtao Wang (Taylor & Francis Group, 2018)
Annonaceous acetogenins (ACGs) are one of the most active constituents isolated from Annona species with potent antitumor activity. However, the poor solubility and severe side effect greatly limit their use in clinic. In this study, folic acid (FA) modified annonaceous acetogenins nanosuspensions (FA-PEG-ACGs-NSps) had been successfully prepared using DSPE-PEG-FA and soybean lecithin (SPC) as stabilizers. The resultant FA-PEG-ACGs-NSps had a mean particle size of 119.7 nm, a zeta potential of -23.0 mV and a high drug payload of 49.68%. The obtained ACGs-NSps had a good stability in various physiological media, and showed sustained drug release. Compared to common ACGs nanoparticles (PEG-ACGs-NSps), FA-PEG-ACGs-NSps showed significantly enhanced in vitro cytotoxicity against folate receptor-positive HeLa cell lines (IC50, 0.483 μg/mL vs. 0.915 μg/mL, p < .05), which could be effectively reversed simply by pretreatment of free FA. In vivo experiments demonstrated that FA-PEG-ACGs-NSps brought more drug molecules into tumors and greatly improved the antitumor efficacy (TIR, 76.45% vs. 25.29%, p < .001). Therefore, DSPE-PEG-FA is considered as a proper stabilizer with active targeting effect for ACGs-NSps to reduce toxicity, enlarge the safe dosage range and apply in clinic for the treatment of folate-positive tumors. Therefore, FA-PEG-ACGs-NSps may be a prospective drug delivery system for ACGs to improve their therapeutic window and find application in clinic to treat FR over-expressed tumors.